Meningkatkan Motivasi Belajar Peserta Didik Kelas VII B SMP Yos Sudarso Karawang Pada Materi Peran Orang Lain Bagi Perkembanganku Melalui Model Discovery Learning - Agustina Ayut; Veronica Nurhayati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The Merdeka Belajar (Emancipated Learning) curriculum requires teachers to think creatively and innovatively in finding solutions to students' various learning problems so that they develop optimally in personality and learning outcomes. The development of these students is within the framework of the Pancasila Student Profile. In this curriculum, teachers have many choices of teaching tools to suit student needs based on projects. One learning model that can be used is Discovery Learning, which helps students get used to finding answers to the problems they face. On this occasion, research using the Discovery learning model was carried out in Class VII B of Yos Sudarso Middle School, Karawang. The aim of the research is to increase students' learning motivation. The type of research used is descriptive qualitative. Meanwhile, data collection used are questionnaires and interviews.